Aplikasi Sistem Informasi Geografis (SIG) Pendataan Pada Pengawasan Dan Pengendalian Menara Telekomunikasi Berbasis Android (Studi Kasus Dinas Komunikasi Dan Informatika Kota Cimahi) - Syani, Mamay; Mahdani; Laia, Firdaus; Mulyana, Dadan; Yudi Permana, Nana (Fakultas Teknik Jurusan Sistem Informasi Universitas Galuh, 2024)
A Geographic Information System (GIS) application based on Android is used for the purpose of data collection and monitoring of telecommunication towers, with a case study conducted at the Department of Communication and Informatics (Diskominfo) of Cimahi City. The aim of this research is to optimize the process of data collection and monitoring of telecommunication towers through the utilization of Android-based technology and geographic information. The hope is that the developed application will provide efficient support for Diskominfo in data management, accurate monitoring of telecommunication tower locations, and enhanced supervision of this crucial infrastructure. By combining Android technology and GIS features, it is expected that this application can become an effective tool in supporting the monitoring and control of telecommunication towers in Cimahi City. The methodology used in designing this system is the Waterfall Software Development Life Cycle (SDLC) methodology, which consists of seven stages: Requirement Definition, Design, Development, Testing, Implementation, Maintenance, and Evaluation. This application is built using Flutter version 3.10.6. From the results of the conducted User Acceptance Test (UAT), the average parameter scores are as follows: user interface (85.6%), application performance (88.4%), application functionality (88.4%), application security (80%), and final feedback (91.4%). The overall test result is 86.7%.